Bromalites from the Ameghino (=Nordenskjöld) Formation Upper Jurassic of Antarctic Peninsula - Bigurrarena Ojeda, Mauricio Andres; Gouiric Cavalli, Soledad; Pérez, Leandro Martín; Reguero, Marcelo Alfredo (Publicación Electrónica de la Asociación Paleontológica Argentina)
We present the study of the bromalites retrieved from the Upper Jurassic Ameghino (=Nordenskjöld) Formation at Longing Gap in the Antarctic Peninsula. The material was morphologically and chemically analyzed. We made a qualitative study and a taphonomic analysis of the specimens and tested paleobiological and paleoecological hypotheses. We conclude that the samples analyzed are coprolites and propose a new ichnotaxon, Antarctoscoprus longinensis ichnogen. and ichnosp. nov., characterized by being a small and flat coprolite differing from other ichnogenera by its composition, which consists mainly of actinopterygian remains (e.g., scales, vertebrae, skull bones, and teeth). Antarctoscoprus longinensis includes three morphotypes (i.e., circular, subcircular, and elongated) derived from an elongated three-dimensional original form by compactation. Based on the internal content, we infer the producers of the coprolites were carnivorous predators, putatively an ichthyophagous taxon. Due to the abundance of actinopterygians—mainly aspidorhynchids and ichthyodectids— and the size of the coprolites we propose macropredator fishes as the putative producers. The mainly undisrupted fish carcasses and coprolites allow us to conduct further studies that might lead to a better understanding of the ancient communities living in the Late Jurassic Sea that surrounded Antarctica. Presentamos el estudio de los bromalitos recuperados de la Formación Ameghino (=Nordenskjöld) del Jurásico Superior en Longing Gap, en la Península Antártica. El material fue analizado morfológica y químicamente. Realizamos un estudio cualitativo y un análisis tafonómico de los especímenes y pusimos a prueba hipótesis paleobiológicas y paleoecológicas. Concluimos que las muestras analizadas son coprolitos y proponemos un nuevo icnotaxón, Antarctoscoprus longinensis ichnogen. e ichnosp. nov., caracterizado por ser un coprolito pequeño y plano que se diferencia de otros icnogéneros por su composición, que consiste principalmente en restos de ...